Pentingnya Perencanaan dan Pengendalian Persediaan Bahan Baku Paving Dengan Metode Economic Order Quantity (EOQ) Untuk Optimalisasi Laba - Zulaikhok Nuraini; Hartirini Warnaningtyas; Mutmainah Mutmainah (Sekolah Tinggi Ilmu Bisnis Kumala Nusa Yogyakarta, 2023)
This study aims to determine optimal raw material purchasing planning using the EOQ (Economic Order Quantity) approach at the Somber Berkah Sukosari Dagangan Madiun Regency company and to provide input regarding planning and controlling raw material inventory so that it has the potential to increase profit efficiency in the company. This study uses a quantitative descriptive method. The descriptive analysis technique used to analyze data regarding the problem of planning and controlling raw materials to optimize company profits is to use the EOQ (Economic Order Quantity), TIC (Total Inventory Cost), Safety Stock, Reorder Point, MI (Maximum Inventory) methods. From the research results it is known that the purchase of raw materials using the EOQ method total raw material inventory is less than using the method used by the company today. Besides, the frequency of purchasing raw materials using the EOQ method is smaller than using the company's method. In addition, there are also safety stocks, reorder points and MI (Maximum Inventory) that have been calculated, so that they can anticipate excess or shortage of raw material supplies. Therefore the EOQ method is very important to be applied in companies in order to achieve more optimal company profits.